Direct Electrochemistry of Catalase Immobilized at Polymerized-SnO2 Multiporous Modified Electrode for an Amperometric H2O2 Biosensor - Alim, Samiul; Jaya Vejayan, Palliah; A. K. M., Kafi (Biomedical Research Network, 2018)
A novel amperometric H2O2 biosensor based on immobilization of catalase with polymerized MPNFs of SnO2 onto glassy carbon electrode with chitosan have been proposed in this work. Multiporous nanofibers of SnO2 were synthesized by electrospinning method from the tin precursor by controlling the concentration followed by polymerized with aniline. Catalase was then co-immobilized with the polymerized nanofibers on the surface of glassy carbon electrode by using chitosan. The polymerized MPNFs of SnO2 play a significant role in facilitating the electron exchange between the electroactive center of catalase and the electrode surface. Cyclic Voltammetry and amperometry were used to study and optimize the performance of the fabricated H2O2 biosensor. The PANI/SnO2-NFs/Catalase/Ch/GCE biosensor displayed a linear amperometric response towards the H2O2 concentration range from 10 to 120M with a detection limit of 0.6M (based on S/N=3). Furthermore, the biosensor reported in this work exhibited acceptable stability, reproducibility, and repeatability.